2014
DOI: 10.1001/jamapsychiatry.2014.652
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Major Disaster on the Mental Health of a Well-Studied Cohort

Abstract: IMPORTANCE There has been growing research into the mental health consequences of major disasters. Few studies have controlled for prospectively assessed mental health. This article describes a natural experiment in which 57% of a well-studied birth cohort was exposed to a major natural disaster (the Canterbury, New Zealand, earthquakes in 2010-2011), with the remainder living outside of the earthquake area.OBJECTIVE To examine the relationships between the extent of earthquake exposure and mental health outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
210
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(236 citation statements)
references
References 42 publications
20
210
0
6
Order By: Relevance
“…Previous studies have provided ample documentation of the impact of exposure to natural disasters on the mental health of survivors (Fergusson et al, 2014; Frankenberg et al, 2008; Kumar et al, 2007; van Griensven et al, 2006). Personal experience of property damage, loss of family and disruption of employment each has been linked to an increased incidence of PTSD, depression and anxiety among survivors (van Griensven et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have provided ample documentation of the impact of exposure to natural disasters on the mental health of survivors (Fergusson et al, 2014; Frankenberg et al, 2008; Kumar et al, 2007; van Griensven et al, 2006). Personal experience of property damage, loss of family and disruption of employment each has been linked to an increased incidence of PTSD, depression and anxiety among survivors (van Griensven et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…10 To the best of our knowledge, only two studies examining mental health status prior to disaster events have been conducted. 11 12 Both studies suggested that major disaster was associated with an increase in the risk for common…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the study closest to this is the Christchurch study [6] which, while generating important findings, only included~1000 participants, limiting what could be studied. Three years is much longer than most clinical follow-ups; longer follow-up would increase costs while lowering follow-up rates.…”
Section: Three-year Follow-up Too Shortmentioning
confidence: 99%